PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP KETERAMPILAN BERBICARA SISWA KELAS IV GUGUS 1 KECAMATAN WAWO - Astuti Mulyaningsi; Ida Bagus Kade Gunayasa; Muhammad Irawan Zain (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2021)
This study aims to determine the effect of the CTL learning model assisted by the Bima folklore on the speaking skills of the fourth grade students at Cluster 1 of Wawo District. The results of this study are expected to be theoretically and practically useful. This study was an experimental research with a quasi experimental design type nonequivalent control group design. The population of this study was all fourth grade students of Elementary School at cluster I of Wawo District academic year 2020/2021 with 86 students in total, consisting of SDN 2 Maria, SDN Inpres Ntori, SDN 3 Maria, and SDN Inpres Kombo. The sampling technique of this research was cluster random sampling type of probability sampling with grade 4 of SDN 3 Maria and SDN Inpres Kombo students as the sample. The data collection method in this study was a test of students' speaking skill used an assessment rubric (pretest-posttest). Data analysis was carried out by using the normality test, homogeneity test and hypothesis test used the polled variance of t-test formula. Hypothesis test at 5% significant level produced tcount = 4.80 while ttable = 1.687, in other words tcount> ttable. Based on the test criteria, if t_count> t_table, then H0 is rejected and Ha is accepted. Therefore, it can be concluded that there is an effect of the CTL learning model assisted with the Bima folklore on the speaking skills of the fourth grade students at cluster I Wawo District in the academic year 2020/2021. Thus it can be stated that the learning model of Contextual Teaching And Learning (CTL) with the help of the Bima folklore can be applied in grade IV elementary school students to improve speaking skills.